Smart Universities: A Concept Overview of Adaption Challenges for Historically Black Universities in South Africa - Victor H. Mlambo; Hlanganani Mnguni; Zubane Sphephelo (NUST Journal of Social Sciences and Humanities)
Universities today are experimenting with AI and big data to improve how students live